2021
DOI: 10.1080/14763141.2020.1856916
|View full text |Cite
|
Sign up to set email alerts
|

Footstrike patterns and race performance in the 2017 IAAF World Championship men’s 10,000 m final

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Direction of foot strike pattern change only recorded as either NRFS to RFS or RFS to NRFS. Data not included if studies reported further sub-categorisation of FFS or MFS d Hanley et al [ 19 ] = 6 checkpoints included in study, first two checkpoints removed due to violating exclusion criteria of being within 2 km of start line and final checkpoint removed as it violated exclusion criteria of being within 1 km of finish line. Performance data considered to be N/A as no competitors recorded as RFS for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Direction of foot strike pattern change only recorded as either NRFS to RFS or RFS to NRFS. Data not included if studies reported further sub-categorisation of FFS or MFS d Hanley et al [ 19 ] = 6 checkpoints included in study, first two checkpoints removed due to violating exclusion criteria of being within 2 km of start line and final checkpoint removed as it violated exclusion criteria of being within 1 km of finish line. Performance data considered to be N/A as no competitors recorded as RFS for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…d Hanley et al [ 19 ] = 6 checkpoints included in study, first two checkpoints removed due to violating exclusion criteria of being within 2 km of start line and final checkpoint removed as it violated exclusion criteria of being within 1 km of finish line. Performance data considered to be N/A as no competitors recorded as RFS for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations